Quantification of NaOH and KOH Tests for Varietal Identification in Traditional Rice Varieties - A New Approach - K SIVARANJANI; K RAJA (Seed Research, 2026)
Traditional varieties in rice are gaining momentum because of its nutritive value. The seed production and use of such varieties in breeding programme are the trends now. Therefore, the genetic purity and its identification are necessary. Hence, an experiment to explore the possibility of quantifying the chemical tests viz., NaOH and KOH for varietal identification and genetic purity assessment in traditional rice varieties was conducted in the Department of Seed Science and Technology, Seed Centre, Tamil Nadu Agricultural University, Coimbatore, India. The results indicated that the traditional rice varieties have large variations in grain colour and thus, it is considered an important trait for varietal characterization and identification. In parallel, the chemical tests viz., NaOH and KOH also showed better differences among the varieties and these tests can very well used for the identification of red grain and white grain varieties. In addition, the measurement of colour absorbance of the NaOH and KOH tests through UV-Visual Spectrophotometer at 430 nm and colour intensity by Tintometer can be used for further differentiation of the varieties.